'Uppity civilians' and 'cyber-vigilantes': The role of the general public in policing cyber-crime. (February 2013) - Huey, Laura; Nhan, Johnny; Broll, Ryan
The distributed nature of the Internet requires that security issues be addressed through collaborative efforts within and across various sets of public and private actors. Drawing on nodal governance theory, this article explores one aspect of the role that the general public can and does play in the field of cyber-security: civilian policing of the Internet. In particular, we examine the motives and actions of regular citizens, who use their computer skills to identify, track and collect information on the activities of suspected criminal offenders. Whereas some groups use such information to engage in vigilante acts, the groups that we study work cooperatively with police, collecting information to pass onto criminal justice agencies. We suggest that these collectives and their members are a potentially useful, if under-valued, component of cyber-security networks.